Analisis Penerapan Fatwa MUI Wisata Halal (Studi Kasus Hotel Syariah Medan) - Riyan Pradesyah; Khairunnisa , (UMSU, 2018)
The purpose of this study was to find out whether sharia hotels in the Medan city had implemented the MUI Fatwa, related to halal tourism. The method used in the study is a qualitative method, comparing the theory with the events in the field. The results obtained, that sharia hotels in the city of Medan have implemented regulations issued by the MUI on halal tourism, which is regulated in No.108 / DSN-MUI / X / 2016. This is shown by the facilities of places of worship such as mushalah, the unavailability of food and drinks, the pornography sites that are on the internet access, not receiving guests who are not Muslims.